Pathophysiology of shock, sepsis, and organ failure - Schlag, Günther; Redl, Heinz (Springer, 1993)
The decisive factor in trauma is that many processes first occur at the cellular level before they can be determined in laboratory tests, and recognition of them has only recently found its way into intensive care practice. Yet knowledge of the pathophysiology of these processes is essential for an early diagnosis of multiple organ failure and the implementation of adequate therapy, which ultimately make the patient\'s survival possible. Professor Schlag, an internationally renowned scientist and clinician, has been concerned with the basic pathophysiological principles of shock for many years. In this book he has brought together for the first time an international team of authors primarily from the USA and Europe, who present their collective findings of trauma, shock, development of the organ in shock and early failure and of sepsis-like syndrome, and development of septic multiple organ failure. Patienten mit Multiorganversagen haben immer noch eine schlechte Prognose in der intensivmedizinischen Behandlung, insbesondere wenn sie noch zusätzlich in einen septischen Schock geraten. Hier hilft auch oft eine breite Abdeckung mit modernsten Antibiotika nicht weiter. Neue Ansätze für eine Therapie dieser problempatienten haben sich in den letzten Jahren durch Erkenntnisse der pathophysiologischeen Vorgänge die zum Schock führen ergeben. Herr Professor Schlag hat als anerkannte Kapazität auf dem Gebiet der Traumatologie und Schockforschung für dieses erste umfassende Werk zu den Grundlagen des Multiorganversagens eine beeindruckende Liste von mehr als 50 international renommierten Autoren zusammenbekommen. Das Buch ist nicht nur eine Aufarbeitung aller Grundlagen des Schocks und Multiorganversagens sondern zudem ein ausgezeichnetes Nachschlagewerk für jeden intensivmedizinisch tätigen Klinikarzt, egal ob er aus der Anästhesie, der Inneren Medizin oder der Unfallchirurgie kommt.
Keywords: sepse; Sepsis; Shock, Traumatic; traumatologie; fyziologie; Syndrome Multi-Organ-Dysfunction; traumatický šok; šok; Shock; patologie; Multiple Organ Failure; multiorgánové selhání